2008
DOI: 10.1007/s00464-008-9904-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of laparoscopic versus open adrenalectomy for sporadic pheochromocytoma

Abstract: Background Laparoscopic adrenalectomy for pheochromocytoma remains subject of debate, owing to the systemic consequences of pneumoperitoneum in patients with catecholamine-secreting tumors. Methods A prospective randomized study was conducted (2000)(2001)(2002)(2003)(2004)(2005)(2006), evaluating cardiovascular instability during open (n = 9, group A) or laparoscopic (n = 13, group B) adrenalectomy for pheochromocytoma. Haemodynamic parameters were recorded by invasive monitoring. Results Haemodynamic instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 18 publications
2
50
0
4
Order By: Relevance
“…4 Once the adrenal neoplasm is diagnosed, resection is the only curative treatment. Although some reports have concluded that laparoscopic adrenalectomy is safe, effective, and minimally invasive, [5][6][7] it is considered a gold standard in Post-contrast computed tomography axial plane shows the mass pressurizing liver forward and laterally. Outside area of the mass displays significant enhancement with uneven thickness.…”
Section: Discussionmentioning
confidence: 99%
“…4 Once the adrenal neoplasm is diagnosed, resection is the only curative treatment. Although some reports have concluded that laparoscopic adrenalectomy is safe, effective, and minimally invasive, [5][6][7] it is considered a gold standard in Post-contrast computed tomography axial plane shows the mass pressurizing liver forward and laterally. Outside area of the mass displays significant enhancement with uneven thickness.…”
Section: Discussionmentioning
confidence: 99%
“…haemodynamic disorders due to excessive manipulations [5]. Currently, the minimally invasive adrenalectomy is successfully used in more than 90% of phaeochromocytoma cases, preceded by preoperative pharmacotherapy to inhibit the hormonal activity of the tumor [6][7][8][9].…”
mentioning
confidence: 99%
“…Tumors of more than 12 cm in diameter and malignant lesions infiltrating other tissues should be operated using conventional approaches [3,7]. In the case of malignant non-infiltrating tumors of 4 to 6 cm, both open and minimally invasive approaches to adrenalectomy are acceptable [11].…”
mentioning
confidence: 99%
“…Recent studies had confirmed that laparoscopic adrenalectomy is a safe and effective treatment for pheochromocytoma [23][24][25][26][27][28]. Patients who had laparoscopic adrenalectomy for pheochromocytomas had shorter mean operating time and hospital stay; less intraoperative hypertension or intraoperative blood loss; less postoperative analgesia requirement, and earlier return to oral nutrition [26].…”
Section: Discussionmentioning
confidence: 99%